Investigate The Different Effect Of Nicotine On H460 And H441 Lung Cells Viability - Mohammed, Bushra Jasim (AL-Kindy College Medical Journal, 2019)
Background: Nicotine is the foremost chemical constituent responsible for addiction in tobacco products, in the non-ionized condition can be easily absorbed via epithelial tissue of the lung, the mouth, the nose  and across the skinObjective:The study examines the harmful effect of   the nicotine which is an important component of cigarette in vitro.Type of the study: Cross-sectional study.Methods: Examines the harmful effect of   the nicotine which is an important component of cigarette in vitro by using two types of lung cancer cell lines (H460 TP53+/+, H441 TP53-/-).Results: The results showed the total count of H460( TP53+/+) cancer lung cell lines  was (5.2 ×106 cells /ml) , the number  (4.9 ×106 cells /ml)  of them were alive  and (3.6×105 cells /ml) of them  were dead, with percentage  of viability (93.15%), while the total count  of H441( TP53-/-) lung cancer cells was (5.1 ×106 cells /ml), the number (4.1 ×106 cells /ml)  of them were alive, and the number (9.9×105 cells /ml) of them   were dead  with percentage  of viability (80.55%). And it  revealed that the nicotine inhibited viability of H460 lung cancer cell lines in all concentrations (1, 10, 500 and 1000 μ M) and the cells were completely abolished by treatment with (1000 μ M) when the viability reached to minimum percentage (3.43%), while nicotine induced proliferation in H441 lung cancer cell lines even in lowest concentration (1 μ M), whereas the viability reached to maximum percentage (41.04%) at concentration (1000 μ M). Also it noticed that  the treatment with nicotine at concentrations (1,10, 500 and 1000 μ M ) for 24 and 48 hr  induced the apoptosis but not necrosis in H460 lung cancer cell lines, especially at the highest concentrations (1000 μ M) for 48hr when the percentage of apoptosis reached to the maximum value (55.5%), however  it was induced proliferation in H441 lung cancer cell lines with highest proliferation at concentration (1000 μ M), when the percentage apoptosis value reached to the minimum percentage (1.5%) when compared to un treated  cells (control).Conclusions: the cells lack to TP53(H441 TP53-/-)  will proliferate when exposed to nicotine and some of these cells will suffer from necrosis as a replacement of apoptosis.